Sukharev O. S. Development of Socio-Economic Potential of Russia: Theory and Practice - Sukharev, Oleg Sergeyevich (Economy of Regions, 2016)
The question of assessing and using the socio-economic potential of Russia is considered within the fundamental monograph prepared on the basis of the Institute of Economics of the Ural Branch of the Russian Academy of Sciences. The main achievements of the large research of the problem of the Russian socio-economic potential conducted by a group of authors with the definition of the most rational and important suggestions for the prospects of the Russian economy are allocated. Certain critical comments are noted, and the authors position is specified concerning the policy of the new industrialization and innovative development within the modern scientific polemic about the subject and tools of economic policy, and also the need ofensuring it by the system efficiency. The main achievement of the presented teamwork of the scientists of the Ural economic school is the development of a methodological framework and hardware (techniques, models) of the diagnostics of the socio-economic potential of the economic system of any level of complexity (despite the main specialization of this school on the regional research) and measuring base. These achievements will give the chance of more exact identification of a condition of the system and definition of the direction of its movement, which will make it possible to affect the mode of this dynamics by the economic policy of regional and federal level.